Exploring rugby coaches perception and implementation of performance analytics - Callinan, M. J.; Connor, J. D.; Sinclair, W. H.; Leicht, A. S. (PLOS ONE, 2023)
Professional coaches commonly rely on performance analysis and metrics to help make decisions regarding their practices, selection and tactics. However, few studies to date have explored coaches` perspectives of performance analysts successful integration into the high-performance environment. The aim of this study was to investigate coaches` philosophies surrounding performance analysis and how they perceived analysts could support and implement these approaches into coaching practices and match preparation. Semi-structured interviews were conducted with five professional elite level Rugby Union coaches to investigate their perceptions of performance analysis, and the contribution of performance analysts to the high-performance environment. Results revealed three main dimensions, including the role, purpose, and desired attributes of a performance analyst. Firstly, the role of the analyst was described in terms of being an information specialist, who collects, filters, and delivers information to stakeholders, and a generalist, who helps coaches utilise technology. Secondly, the purpose of the analyst was described in terms of providing both accountability and support for coaches and players. Finally, the attributes needed of an analyst included the ability to form a close relationship with coaches, communicate complex information in meaningful ways, and who was proactive, innovative, and creative when tasked with delivering information. The findings highlighted the crucial roles, purposes, and attributes of a performance analyst within high-performance Rugby Union identified by coaches and the importance of the coach-analyst relationship to support these dimensions.